Effects of Flaxseed Oil Consumption on Anthropometric Parameters in the Patients with Metabolic Syndrome: A Randomized Clinical Trial: - Akrami, Atefeh; Babajafari, Siavash; Faghih, Shiva; Zibaeenejad, Mohammad Javad; Nikaein, Farzad (Galen Medical Journal, 2017)
Background: Flaxseed oil, as the main source of Alpha linolenic acid (ALA), decreases the production of Arachidonic acid (AA) from linoleic acid (LA) that plays an important role in the development of metabolic syndrome (MS). The aim of the present study was to compare the effects of flaxseed oil and sunflower oil on anthropometric parameters in patients suffering from MS. Materials and Methods: In this randomized clinical trial, 60 participants aged 30-60 years who suffered from MS were selected according to ATP III definition and were divided into two even groups receiving flaxseed oil and sunflower oil. Each group received 25 ml of the specified oil on a daily basis for 7 weeks. The anthropometric measures were evaluated on the first and last days of the study. Results: No significant differences were observed between the two groups regarding weight. However, waist circumference reduced significantly in the flaxseed oil group compared to the control group (P=0.001). Conclusions: The ALA might prevent the increase in adipose tissues. Therefore, it seems that flaxseed oil has beneficial effects on MS. [GMJ.2017;6(1):44-51]